Pengaruh Tangible, Empathy Dan Assurance Terhadap Keputusan Pembelian Pada PT. Raden Auto Jakarta - Hendry Syahrial; M. Rizan (Manajerial, 2015)
The objectives of this study were determining the effect of tangibles, empathy, and assurance on the decision to buy at PT Raden auto, Jakarta. This study uses a quantitative approach to data collection techniques using questionnaires. The populations used in this study are the consumer at PT. Raden Auto Jakarta, while the sample using purposive sampling technique, which determines the sample by chance, in order to obtain the total sample of 100 people. The results showed that the tangibles, empathy, and assurance were predicted by decision to buy. In other words, learning strategies has been a role in increasing tangibles, empathy, and assurance customers in the PT Raden Auto, Jakarta. The results proved that decision to buy was simultaneous affected by tangible, empathy, and asssurance.